Levels of Entrepreneurial Tendency and of Interpersonal Communication Competence of Students in an Associate Degree in Hospital Management Course - Costa, Theo Duarte da; Salvador, Pétala Tuani Candido de Oliveira; Brilinger, Caroline Orlandi; Santos, Fernanda Julyana Silva dos; Pereira, Sirlene Silveira de Amorim (O Mundo da Saúde, 2023)
The objective of this study was to identify the entrepreneurial tendency and the level of interpersonal communication competence of students of the associate degree in Hospital Management (HM) course. A cross-sectional, quantitative, multicenter study was carried out, which brought together two of the four federal institutions that offer the course in Brazil. Data collection took place online, in July 2021, using an electronic form consisting of three sections: characterization of participants; the General measure of Enterprising Tendency (GET) test; and the Interpersonal Communication Competency Scale (ICCS). Descriptive and inferential statistics were used for data analysis. The sample consisted of 142 students, with a mean age of 26.65 (±8.8) years old, and a prevalence of women (109; 76.8%) and of students who attended high school entirely in the public school system (95; 66.9%). The GET dimension with the best performance was “Impulse and Determination”, with an average of 9.08. In the dimensions “Creative Tendency” and “Propensity toward Calculated Risks”, no participant obtained the maximum score. As for the ICCS, the total average (65.10) revealed a good level of competence in interpersonal communication. The highest average obtained was in the “Self-disclosure” domain, while the lowest was in the “Interaction Management” domain. A very low level of general entrepreneurial tendency and a good level of competence in interpersonal communication in the students of the HET course in Hospital Management were elucidated, which reveals possible ways to improve the entrepreneurial education of this course.